Studying Points of Difference in Body Parts’ Center of Weight And Their Relation to Rhythmic Balance of Female Students - Alheli, Mohammed; Alsafaah, Ragdaa; Azaab, Nabel (Journal of Physical Education, 2019)
The aim of the research was to study the points of difference in the centers of the weight of the different parts of the body and relationship rhythmic balance of female students in the Physical Education and Sport Sciences College / University of Babylon. The researchers hypothesized statistical significant relationship between the points of difference in body parts’ weight centers and rhythmic balance in female students in Physical Education and Sport Sciences College/ University of Babylon. The researchers used the descriptive method on (6) first year female students of Physical Education and sport sciences college / University of Babylon. The data were collected and treated using (SPSS) to conclude that there is weak correlation between the points of difference in body part weight centers on rhythmic balance in female students. In addition to that, the researchers concluded that rhythmic tone play an active role in organizing the incoming and outgoing nerve waves which increases with achieved sensory – motor perception.